GNSS Anti-Multipath Technology of UAV for Geological Hazard Monitoring - FENG Jianhui; YANG Xiuzheng; MA Wenliang; SHEN Feng (Journal of Harbin University of Science and Technology)
A GNSS-based UAV anti-multipath technology for geological hazard monitoring is proposed to ensure the positioning capability of UAVs in complex environments. This method designs a non-coherent phase detector utilizing the S-curve shaping based on cosine phase Binary Offset Carrier (BOC) signal. Compared with other structures of multiple correlators, the proposed method only needs to calculate two linear combination codes by the least square method, and the product of the cross-correlation function between the received signal and the two local combination codes is used to obtain an asymmetric S-curve without any false lock points. The simulation results show that the method has multipath suppression ability and can also achieve unambiguous tracking of BOC signals.